Histopathological features of thrombotic microangiopathies in renal biopsies - Miguel Ernandes Neto; Lucas de Moraes Soler; Halita Vieira Gallindo Vasconcelos; Daniela Cristina dos Santos; Rosa Marlene Viero; Luis Modelli Gustavo de Andrade (Society of Diabetic Nephropathy Prevention, 2019)
Background: Thrombotic microangiopathy (TMA) is a morphologic lesion characterized by thrombi occluding microvasculature related to endothelial injury. Objectives: This study aimed to assess the association between histopathological findings and etiology of TMA. Patients and Methods: This cross-sectional study comprised a sample of 34 patients who underwent renal biopsy and received an initial TMA diagnoses resulting in 29 definitive TMA cases. We evaluated the TMA features and clinical histopathological correlation. Results: The most frequent etiologies were atypical hemolytic uremic syndrome (aHUS) (n= 10; 34.5%), hemolytic uremic syndrome caused by Shiga toxin-producing Escherichia coli (STECHUS) (n=6; 24.1%) and secondary causes of TMA (n= 12; 41.4%). We found the following histological features; patients with aHUS had thrombi in 60% of biopsies, membranoproliferative glomerulonephritis (MPGN)-like pattern in 20% and ischemia in 20%; patients with STEC-HUS had thrombi (14.3%), MPGN-like pattern (14.3%), endothelial swelling (14.3%) and ischemia (57.1%); patients with secondary etiologies had thrombi (58.3%), endothelial swelling (16.7%), ischemia (16.7%) and MPGN-like pattern (8.3%). Conclusions: The distribution of classic TMA findings was not related to etiology in spite of microthrombi having been found mostly in aHUS and secondary etiologies, whereas ischemia was found mainly in STEC-HUS. We did not find a histopathological pattern to each etiology of TMA.